2020
DOI: 10.3390/cells9040848
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sphingomyelinase Downregulation Enhances Mitochondrial Fusion and Promotes Oxidative Metabolism in a Mouse Model of Melanoma

Abstract: Melanoma is the most severe type of skin cancer. Its unique and heterogeneous metabolism, relying on both glycolysis and oxidative phosphorylation, allows it to adapt to disparate conditions. Mitochondrial function is strictly interconnected with mitochondrial dynamics and both are fundamental in tumour progression and metastasis. The malignant phenotype of melanoma is also regulated by the expression levels of the enzyme acid sphingomyelinase (A-SMase). By modulating at transcriptional level A-SMase in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Interestingly, patients who suffer from LSDs exhibit dysfunctional mitochondria, impairment of autophagy and accumulation of cytoplasmic protein aggregates [ 29 , 30 ]. Moreover, recently Coazzoli et al showed that another key enzyme in sphingolipid metabolism, acid sphingomyelinase, has an important role in the regulation of mitochondrial function and morphology in melanoma cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients who suffer from LSDs exhibit dysfunctional mitochondria, impairment of autophagy and accumulation of cytoplasmic protein aggregates [ 29 , 30 ]. Moreover, recently Coazzoli et al showed that another key enzyme in sphingolipid metabolism, acid sphingomyelinase, has an important role in the regulation of mitochondrial function and morphology in melanoma cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purified RNA was then reverse transcribed into cDNA with MultiScribe Reverse Transcriptase, oligo(dT), and a random hexamer primer mix (all from Applied Biosystems Life Technologies, CA, USA). Quantitative evaluation of the target gene was then performed by using an ABI Prism 7500 sequence detection system (Applied Biosystems Life Technologies) with Power SYBR Green PCR Master Mix reagent and specific primers (mSREBP2: sense, 5′-gcgttctggagaccatgga-3′, antisense, 5′-acaaagttgctctgaaaacaaatca-3′; mGK [19]: sense, 5′-ccctgagtggcttacagttc-3′, antisense, 5′-acggatgtggagtgttgaagc-3′; mGLUT2 [19]: sense, 5′-cctcaagaggtaataatatccc-3′, antisense, 5′-ccatcaagagggctccagtc-3′; mHMGCR [19]: sense, 5′-cttgtggaatgccttgtgattg-3′, antisense, 5′-agccgaagcagcacatgat-3′; mHMGCS: sense, 5′-gccgtgaactgggtcgaa-3′, antisense, 5′-gcatatatagcaatgtctcctgcaa-3′; mPFKFB3 [20]: sense, 5′-ctatcccacgggagagtcc-3′, antisense, 5′-tggcgctctaattccatga-3′; mASMASE [21]: sense, 5′-tgggactcctttggatggg-3′, antisense, 5′-cggcgctatggcactgaat-3′; mG6PD [22]: sense, 5′-ccggaaactggctgtgcgct-3′, antisense, 5′-ccaggtcacccgatgcaccc-3′ and mSLC7A5/LAT1 [23]: sense, 5′-atatcacgctgctcaacggtg-3′, antisense, 5′-ctccagcatgtaggcgtagtc-3′). The PCR cycling conditions were 95 °C (15 s), 40 cycles at 95 °C (15 s), and 60 °C (1 min).…”
Section: Quantitative Real-time Pcr (Rt-qpcr)mentioning
confidence: 99%
“…In B16 cells, chloroquine triggered lysosomal accumulation and oxidative stress, resulting in mitochondrial depolarization and apoptotic/necrotic cell death. In this respect, chloroquine treatment of cells resistant to cisplatin, characterised also by an alteration of oxidative metabolism, led to the re-sensitization to the chemotherapeutic drug through the modulation of mammalian target of rapamycin (mTOR)-mediated autophagy [ 82 , 83 ]. A similar scenario was observed in calorie-restricted mice in which chloroquine reduced melanoma growth and necrosis of tumour cells.…”
Section: Melanoma Cell Death and Survival: Simultaneous Regulation Of Oxidative Stress System And Autophagy Machinerymentioning
confidence: 99%